The Dynamics of Dowry and Maintenance in Marriage: Integrating Tradition, Economy, and Family Welfare in Indonesia - Halum Musthafa; Azizah Mardiyah; Marzuki Hafiz Alhamdani Hasibuan; Ummi Saidah (Abdurrauf Journal of Islamic Studies, 2026)
This study aims to examine the concepts of dowry (mahar) and maintenance (nafkah) in marriage, as well as their impact on the economy and family welfare in Indonesia. Using a qualitative approach through a literature review method, the study analyzes various religious, legal, and previous research sources related to the practice of dowry and maintenance in both customary and Islamic societies. The findings reveal that dowry and maintenance serve not only as legal requirements for marriage but also carry significant symbolic, social, and economic meanings. Dowry traditions vary widely across different regions of Indonesia, ranging from money, gold, traditional items, to unique symbols that reflect local cultural values. The amount and form of dowry are generally determined through family deliberation and are adjusted according to the economic conditions and social status of the bride and groom. Dowry can serve as an economic asset for women, while maintenance is a primary obligation of the husband to fulfill the family’s basic needs. The practice of providing moderate and fair maintenance contributes to family harmony and overall well-being. This study concludes that the dynamics of dowry and maintenance in Indonesia reflect a harmony between religious teachings, local customs, and modern economic demands, and play a crucial role in strengthening the family institution and enhancing the welfare of its members.